STRATEGI BISNIS YANG BERORIENTASI KONSUMEN - Euis Dasipah (Paspalum: Jurnal Ilmiah Pertanian, 2016)
The use of marketing concept philosophy in a company's program is not just an effort of those who are given the responsibility of sales and marketing, but an endeavor attempted by everyone in an organization. Requirements needed for consumer-oriented organizational development include some activities i.e. inculcating consumer-oriented values and beliefs which are supported by top management, integrating markets and consumers into the process of strategic planning, creating marketing management & developing a strong program, creating a basic measurement of performance on the basis of markets, and developing commitment to consumers throughout the organization.